2021
DOI: 10.19128/turje.865344
|View full text |Cite
|
Sign up to set email alerts
|

Emergency remote education in foreign and second language teaching

Abstract: This study aims at tracing the effects of emergency remote education due to Covid-19 on foreign/second language teaching documented in research papers and reports. Employing document analysis, it identifies the research contexts and key findings reported in the studies published between 1 January and 28 October 2020. The findings indicate that a significant number of publications consist of reports presented by practitioners, i.e. schools, governmental authorities and educational foundations, and that the tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…However, the transition from traditional face-to-face classroom-based learning to a fully online learning environment presented a very different experience for both students and educators, and both were expected to adapt quickly to this new situation in just a very short period [ 16 ]. Along with emergency distance education, teachers were asked to utilize information technologies within online educational environments regardless of their digital literacy levels [ 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the transition from traditional face-to-face classroom-based learning to a fully online learning environment presented a very different experience for both students and educators, and both were expected to adapt quickly to this new situation in just a very short period [ 16 ]. Along with emergency distance education, teachers were asked to utilize information technologies within online educational environments regardless of their digital literacy levels [ 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study's primary focus is to examine the interrelationships between COVID-19 quality of life, loneliness, happiness, and Internet addiction among school administrators and teachers. The spread of the epidemic, schools' closure and the transition to distance education started a new process for students, teachers, and school administrators [16]. Uncertainty brought by the pandemic has caused some crises in education, and school administrators and teachers have been negatively affected by this crisis.…”
Section: Introductionmentioning
confidence: 99%
“…For the institution-based component of teacher opinion on emergency remote education, faculty support, and decision making related to pandemic have been analysis study by Akbana et al (2021) showed that support from the school or university has been more frequently reported by the teachers. Similarly, gaining support and training from the faculty has been stated in other studies (Kurnaz & Serçemeli, 2020;Mishra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggested that emergency remote education experience helped instructors' professional development. Akbana et al (2021) found out with their meta-analysis work that most emergency remote English language education studies made it clear that emergency remote teaching helps teachers' technological skills. Saidi and Afshari (2021) stated that English for academic purposes remote instructors believe that remote teaching fosters instructors' professional identity and facilitates access to authentic materials and adds variety to the class activities.…”
Section: Introductionmentioning
confidence: 99%